SOLVING PROBLEMS IN STEREOLOGY WITHOUT MATHEMATICAL FORMALISM - Wojnar, Leszek (Image Analysis and Stereology, 2018)
Scientific work is often very time consuming and the results are frequently not clear for the audience. A sense of humour is a good tool for demonstration of complicated problems. The paper describes selected cases from the past 30 years in which a sense of humour together with appropriate cartoons were successfully applied.